Synergetic Effect of Recoverin and Calmodulin on Regulation of Rhodopsin Kinase - Grigoriev, Ilya I.; Senin, Ivan I.; Tikhomirova, Natalya K.; Komolov, Konstantin E.; Permyakov, Sergei E.; Zernii, Evgeni Y.; Koch, Karl-Wilhelm; Philippov, Pavel P. (Frontiers in Molecular Neuroscience, 2012)
Phosphorylation of photoactivated rhodopsin by rhodopsin kinase (RK or GRK1), a first step of the phototransduction cascade turnoff, is under the control of Ca2+/recoverin. Here, we demonstrate that calmodulin, a ubiquitous Ca2+-sensor, can inhibit RK, though less effectively than recoverin does. We have utilized the surface plasmon resonance (SPR) technology to map the calmodulin binding site in the RK molecule. Calmodulin does not interact with the recoverin binding site within amino acid residues M1-S25 of the enzyme. Instead, the high affinity calmodulin binding site is localized within a stretch of amino acid residues V150-K175 in the N-terminal regulatory region of RK. Moreover, the inhibitory effect of calmodulin and recoverin on RK activity is synergetic, which is in agreement with the existence of separate binding sites for each Ca2+-sensing protein. The synergetic inhibition of RK by both Ca2+-sensors occurs over a broader range of Ca2+-concentration than by recoverin alone, indicating increased Ca2+-sensitivity of RK regulation in the presence of both Ca2+-sensors. Taken together, our data suggest that RK regulation by calmodulin in photoreceptor cells could complement the well-known inhibitory effect of recoverin on RK.